Melampaui Eksegesis dan Eisegesis: Tinjauan Kritis terhadap Hermeneutika Teologi Pembebasan - Agus Kriswanto (Sekolah Tinggi Teologi Sumatera Utara, 2020)
Liberation Theology as a movement and theological method has a unique hermeneutical approach. The way they study the Bible begins with studying their real life situations, then they identify the answers the Bible gives to their real problems. Interpreting the Bible starting from the context by some scholar was considered as an act of eisegesis, and not exegesis. Thus, this paper aims to review the hermeneutical approach used by Liberation Theology movement. This research is a qualitative research using descriptive-analytical method. Liberation Theology's hermeneutical approach is clearly outlined. Furthermore, the analysis of this approach is carried out by tracing its philosophical basis. In this way, one can judge the hermeneutics of Liberation Theology fairly and proportionally. The view being argued in this paper is that criticism of the hermeneutical approach of Liberation Theology is not properly positioned in the contradiction between exegesis and eisegesis, but it needs to be understood as beyond the contradiction. Although this approach starts its hermeneutic circle from context to text, that does not mean it cannot be justified. Pre-understanding before reading the text is raised clearly so that it can be spoken about with the intention of the text being read. It is in the process of dialoguing the context with the biblical text that the